The Economic Impact of Medicaid Expansion on Pennsylvania - Carter C. Price, Julie M. Donohue (RAND Corporation, 2013)
The Affordable Care Act (ACA) includes two provisions that will transfer federal dollars to state economies: an expansion of Medicaid to cover those earning less than 138 percent of the federal poverty level (FPL) and health insurance subsidies for people with incomes between 100 percent and 400 percent of the FPL. These coverage expansions are financed by changes to Medicare payment policy, reductions in Disproportionate Share Hospital (DSH) payments, and new taxes and fees, which transfer money from state economies to the federal government. The June 2012 U.S. Supreme Court decision regarding the ACA gave state governments discretion over whether to expand Medicaid, but most of the other provisions in the ACA— including reductions to Medicare and DSH payments—will occur regardless of how states handle the Medicaid provision. In determining whether to expand Medicaid, Pennsylvania’s stakeholders may wish to consider the ACA’s overall economic effects on the state, both with and without the Medicaid expansion. To inform this policy debate, we estimated the effects of the ACA’s implementation in Pennsylvania (with and without the Medicaid expansion) on rates of insurance coverage (by source), net flows of federal spending, change in gross domestic product (GDP), state employment, state government spending and tax revenues, and uncompensated care costs. To estimate the ACA’s coverage and federal spending impacts, we used the RAND COMPARE microsimulation model. We then applied the Regional Input-Output Modeling System multipliers from the Bureau of Economic Analysis to determine the ACA’s broader economic effects. We estimate these policy effects at the state level and within Pennsylvania’s regions.